Addition of Ge to Cr–Ta–Si laves phase-based alloys. (November 2021) - Wilson, A.S.; Pickering, E.J.; Jones, C.N.; Rae, C.M.F.; Stone, H.J.
Abstract: The Cr–Cr2 Ta system is of interest as a potential candidate for structural applications at temperatures that exceed those that can be tolerated by nickel-based superalloys. However, the oxidation resistance of alloys based on this system is currently insufficient. Previous work on the Cr–Cr3 Si system suggests that Ge additions may also improve the oxidation resistance of alloys based on the Cr–Cr2 Ta system. To ascertain whether such additions may be appropriate, the effect of Ge additions on the microstructure and mechanical properties of a Cr–10Ta–7Si alloy was investigated. The Laves phase in this system was unexpectedly found to decompose into a lamellar structure comprising a Cr solid solution and a cubic phase with an Fd-3m structure. The addition of Ge promotes this decomposition, as well as the formation of the A15 Cr3 (Si, Ge) phase, at the expense of the Cr solid solution. The formation of the A15 phase increases the hardness of the alloy but has a detrimental effect on its ductility. Highlights: Microstructural characterisation of Ge additions to a Cr–10Ta–7Si alloy. Ge promotes A15 phase formation, increasing alloy hardness but reducing ductility. The Laves phase in this system is unstable. The addition of Ge promotes the decomposition of the Laves phase.